2022
DOI: 10.3390/rs14174235
|View full text |Cite
|
Sign up to set email alerts
|

H2A2Net: A Hybrid Convolution and Hybrid Resolution Network with Double Attention for Hyperspectral Image Classification

Abstract: Deep learning (DL) has recently been a core ingredient in modern computer vision tasks, triggering a wave of revolutions in various fields. The hyperspectral image (HSI) classification task is no exception. A wide range of DL-based methods have shone brilliantly in HSI classification. However, understanding how to better exploit spectral and spatial information regarding HSI is still an open area of enquiry. In this article, we propose a hybrid convolution and hybrid resolution network with double attention fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…R. Shang et al [27] proposed a hyperspectral image classification approach (MCRSCA) based on multiscale cross-branching response and second-order channel attention to capture small distinctions between several categories and extract nonlocal contextual information. Additionally, to fully utilize the advantages of multiscale methods and attention mechanisms, Shi et al [28] proposed a multibranch hybrid CNN based on multiresolution and attention mechanisms to emphasize useful spectral-spatial information. Xu et al [29] suggested a multiscale and crosslevel attention learning (MCAL) network to account for both spatial context and spectral information.…”
Section: A Spectral-spatial Feature Extraction Methods In Hsi Classif...mentioning
confidence: 99%
“…R. Shang et al [27] proposed a hyperspectral image classification approach (MCRSCA) based on multiscale cross-branching response and second-order channel attention to capture small distinctions between several categories and extract nonlocal contextual information. Additionally, to fully utilize the advantages of multiscale methods and attention mechanisms, Shi et al [28] proposed a multibranch hybrid CNN based on multiresolution and attention mechanisms to emphasize useful spectral-spatial information. Xu et al [29] suggested a multiscale and crosslevel attention learning (MCAL) network to account for both spatial context and spectral information.…”
Section: A Spectral-spatial Feature Extraction Methods In Hsi Classif...mentioning
confidence: 99%
“…Relevant spatial areas are mainly composed of the pixels which have the same label as the center pixel of the sample. Features extracted from these areas generally reveal the distinctive information of each class [162,171,178]. In this section, techniques to obtain common spatial features and relevant spatial areas are outlined.…”
Section: Extraction Of Discriminating Spatial Featuresmentioning
confidence: 99%
“…Convolution-based spatial attention modules [170,173,175] usually adopt convolutional layers to connect the local correlations between regions with spatial attention. GE modules [169] utilize depth-wise convolution to gather and assess the correlations between spectral features in small regions and resize aggregated weights for adjustment [170][171][172]. To consider more useful information of input, spa-CBAMs [147] introduce global average pooling and max-pooling layers before convolution, which improve spatial attention without increasing the number of parameters [161][162][163][164][173][174][175].…”
Section: Convolution-based Spatial Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al 27 proposed a method based on a consolidated convolutional neural network (C-CNN) composed of 2DCNN and 3DCNN to learn the spatial-spectral features and abstract spatial features of hyperspectral images. Shi et al 28 proposed a model based on multi-scale feature fusion and double attention mechanism to extract features from hyperspectral images. Although the CNN-based models have made some progress in HSI classification, the performance of them is still insufficient.…”
Section: Introductionmentioning
confidence: 99%